Синтез системы оптимального стохастического управления технологическим процессом выращивания органических монокристаллов - Тевяшев, А. Д.; Щелкалин, В. Н.; Суздаль, B. C.; Козьмин, Ю. С. (ХНУРЭ, 2009)
The problem of optimal stochastic control system synthesizing of technological process of organic monocrystals growing was considered for reception of monocrystals with guaranteed characteristics.
Keywords: выращивание органических монокристаллов; органическиймонокристалл